The use of the elaboration likelihood model and Islamic persuasive communication for online persuasion - Mohamad, Nor Atifah; Abdullah, Normah; Suyurno, S. Salahudin (Academy of Contemporary Islamic Studies (ACIS), 2020)
This concept paper explores the online persuasion in the light of Elaboration Likelihood Model (ELM) and the Islamic communication principles. According to ELM persuasion happens between one of the two routes; the central route and peripheral route that lead to behavioural change. Central route processing depends on the strength of the argument or the logical processing of the information whereas peripheral route depends on the contextual clues or other seemingly unimportant cues. As for the Islamic communication principles, this paper presents the two main principles of Islamic communication, which are the tawhidic principle and the doctrine of ma’ruf and munkar and the six Islamic ethics of conversation. Thus, this paper suggests the use of Islamic values and elements together with the two routes of persuasion postulated by ELM in order to create the persuasion process that is permissible from Islamic context. These insights may shed new research direction in term of online persuasion as the proposed framework may further develop the online persuasion that suits the Muslim community.